2020
DOI: 10.31590/ejosat.667689
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Matematik Ders Kitaplarının Matematik Öğretmenleri Tarafından Değerlendirilmesi

Abstract: ÖzBu araştırmanın amacı, ortaokul matematik ders kitaplarını öğretmen görüşlerine göre değerlendirmektir. Bu genel amaç doğrultusunda çalışmada, ders kitaplarının Liselere Giriş Sınavı (LGS)'ye uygunluğu, öğretim sürecinde aktif kullanımı, okullarda uygulanan eğitim müfredatına uygunluğu ve eğitim faaliyetlerindeki ekstra kaynak ihtiyacı da araştırılmıştır. Dolayısıyla araştırmada durum çalışması yapılmıştır. Veriler analiz edilirken içerik analizi yöntemi tercih edilmiş, frekanslara göre kodlar, kodlara göre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…These findings indicate that textbooks should be developed in the context of content that students can understand on their own, and especially in preparation for central exams. Korkmaz, Tutak and Ilhan (2020), who evaluated the 8th-grade mathematics textbook in the context of face-to-face classes, pointed out that as a result of the study, teachers found textbooks insufficient, especially when preparing for the high-school entrance exam. The main purpose of textbooks is to guide the knowledge to be taught (Chevallard & Bosch, 2013), which is obtained by regulating the scientific knowledge of the relevant discipline, accompanied by contemporary teaching approaches and within the framework of the curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate that textbooks should be developed in the context of content that students can understand on their own, and especially in preparation for central exams. Korkmaz, Tutak and Ilhan (2020), who evaluated the 8th-grade mathematics textbook in the context of face-to-face classes, pointed out that as a result of the study, teachers found textbooks insufficient, especially when preparing for the high-school entrance exam. The main purpose of textbooks is to guide the knowledge to be taught (Chevallard & Bosch, 2013), which is obtained by regulating the scientific knowledge of the relevant discipline, accompanied by contemporary teaching approaches and within the framework of the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…and they have been discussed sometimes in the context of Turkey, and sometimes in comparison with some other books belonging to different countries. Turkish Mathematics Textbooks were more often compared with Singapore, Finland, South Korea and American textbooks, and some evaluations were applied in terms of content types and content organization in this process (Engin & Sezer, 2016;Erbaş, Alacacı & Bulut;2012;Korkmaz, Tutak & İlhan, 2020;Sevimli & Kul, 2015;Toprak & Özmantar, 2019;Ulusoy & İncikabı, 2020;Yanık, Özdemir & Çevirgen, 2017). In one of the studies evaluating middle school mathematics textbooks in terms of content and design characteristics, Erbaş, Alacacı and Bulut (2012) compared Turkish, Singapore and American 6 th -grade mathematics textbooks.…”
Section: Textbook Usage In Mathematics Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Katipoğlu ve Katipoğlu (2016), matematik öğretmenlerinin öğrenci ders kitabı hakkındaki görüşlerini inceledikleri araştırmalarında bu sonuçlara benzer şekilde öğretmenlerin metinleri ve soruları yetersiz buldukları sonucuna ulaşmışlardır. Korkmaz, Tutak ve İlhan (2020), ortaokul matematik ders kitaplarını öğretmen görüşlerine göre değerlendirdikleri çalışmalarında bu araştırmanın bulgularına paralel olarak konu anlatımı ile alıştırma ve soruların yetersiz olduğunu bulmuşlardır.…”
Section: Tartışma Ve Sonuçlarunclassified
“…Alışılagelmişten farklı olan bu sınavlar ani ve köklü bir değişimin sonucudur (Güler, Arslan ve Çelik, 2019) ve bu durumun hem öğrenciler hem de öğretmenler için belirsizlikler taşıdığı bir gerçektir (Biber, Tuna, Uysal ve Kabuklu, 2018). Nitekim, bu problemlerin özelliklerine ilişkin "nitelikli", "farklı tarz", "zor", "uzun" ve "anlaşılması kolay olmayan" şeklinde öğretmenlerin tanımlamalarına rastlanmaktadır (Güler vd., 2019;Korkmaz, Tutak ve İlhan, 2020). Bu nedenle bu problemler, tam bir tanımı yapılamamakla beraber, öğretmenler ve öğrenciler tarafından "yeni nesil soru" olarak nitelendirilmiştir.…”
unclassified